Performance of nanolubricants and r1234yf in automotive air conditioning system - Sharif, Mohd Zaki (2021)
Currently, R1234yf refrigerant has been used to replace R134a refrigerant in automotive air conditioning (AAC) systems due to its low global warming potential (GWP) and zero ozone depletion potential (ODP). However, the low performance of the vapour compression in the AAC system using the R1234yf has been a significant hindrance. Hence, a passive method using nanolubricants is proposed to enhance the performance of an AAC system operating with R1234yf. The objectives of this study are to characterize the nanolubricants for AAC system and investigate the performance of AAC system using nanolubricants and R1234yf under experimental and numerical simulated conditions. Aluminium oxide (Al2O3) and Silicon dioxide (SiO2) nanoparticles are dispersed in PAG ND12 lubricant. Al2O3/PAG, SiO2/PAG, and Al2O3-SiO2/PAG nanolubricants were prepared by two-step method of preparation. The stability of the nanolubricants was confirmed by 4-Step Ultraviolet-Visible (UV-Vis) spectrophotometer and zeta potential. Thermo-physical properties namely dynamic viscosity and thermal conductivity evaluation were employed to characterize the novel nanolubricants with PAG ND12 based lubricant. The experimental investigation on the performance of automotive air conditioning system with R1234yf was undertaken for the Al2O3/PAG, SiO2/PAG, and Al2O3-SiO2/PAG nanolubricants at different volume concentrations and various operating conditions. The performance of the AAC system is evaluated by measuring the degree of heat absorption, compressor work and coefficient of performance (COP). The Al2O3-SiO2/PAG nanolubricants with the best performance in the experimental study was selected for further evaluation in simulation study. The simulation analysis of AAC with thermostatic switch using R1234yf and Al2O3-SiO2/PAG nanolubricants at optimum concentration was done to evaluate the behaviour of AAC system in real vehicle conditions. The results from the stability analysis show that the Al2O3/PAG, SiO2/PAG, and Al2O3-SiO2/PAG nanolubricants was confirmed in excellent stability condition for more than 6 months with minimum visual sedimentation, more than 70% concentration ratio and zeta potentials greater than 60 mV. Further, the thermo-physical properties of the nanolubricants showed improvement with increasing of volume concentration. These nanolubricants exhibit some shear thickening properties at low shear rates but show Newtonian behaviour at higher shear rates onwards. The thermal conductivity of the Al2O3/PAG, SiO2/PAG and Al2O3-SiO2/PAG nanolubricants were decreased with increasing temperature but increased with increasing of volume concentration. Al2O3-SiO2/PAG hybrid nanolubricants outperformed others with highest thermal conductivity and intermediate viscosity value between Al2O3/PAG and SiO2/PAG nanolubricants. The AAC-SiO2 system has better cooling capacity performance with enhancement up to 15.7% at 0.01% concentration but slightly decrease in terms of power consumption and COP performance. Meanwhile the AAC-Al2O3 system performed better than AAC-SiO2 system in terms of power consumption and COP improvement with 27.1% average reduction and 9.8% average enhancement, respectively for 0.05% concentration. The COP was improved further for AAC-Al2O3-SiO2 hybrid system with average increment of 12.01% in all test conditions. The dynamic model simulation was confirmed the performance of Al2O3-SiO2/PAG hybrid nanolubricants better than original system with less energy, lower power consumption and higher cooling capacity. The AAC system operating with hybrid nanolubricants has a lesser temperature cycling frequency compared to the AAC system with PAG lubricant. As a conclusion, Al2O3-SiO2/PAG hybrid nanolubricants and R1234yf is recommended for application in AAC system with the improvement of overall system performance.